(untitled) (Vietnam Journal of Community Medicine, 2026)
Problem Statement: The AIDET process is based on five fundamental principles: Building rapport – Introduction – Time Information – Explanation – Thanking, to further improve communication effectiveness between healthcare staff and patients. This communication process is simple, easy to apply, and can be established as a daily communication standard suitable for the healthcare environment, providing healthcare staff with a model for communicating with patients with all the necessary information. The project is developed with two objectives: 1) To describe the current state of nursing communication and some influencing factors at Nghe An Oncology Hospital in 2025. 2) To propose solutions to improve the effectiveness of nursing communication according to the AIDET process at Nghe An Oncology Hospital in the period 2025-2027. Method: The data collection process was conducted from April to July 2025. The study involved observing the communication skills of 150 nurses with patients (one interaction per nurse), conducting in-depth interviews with one hospital leader, one head of the nursing department, and organizing a focus group discussion with 12 nurses directly involved in patient care from the surveyed clinical departments. Results: The results showed that the compliance rate of nurses with the AIDET procedure was 43.3%. The lowest compliance rates were observed in the step of nurses saying thank you after completing patient care (29.3%) and nurses greeting patients politely by their first name upon contact and before care (66%). The lowest nonverbal communication skill compliance rates were for "Smiling facial expressions, creating a friendly atmosphere" (74.0%) and "Appropriate tone and speaking speed" (78.7%). Some shortcomings in the implementation of the AIDET communication process include: the lack of a steering committee for implementing the AIDET process and developing an implementation plan; young nurses lacking experience in handling situations; training sessions lacking simulations of real-life situations for application; insufficient monitoring and evaluation of communication skills; hospital overcrowding; and a lack of policies and regulations on communication behaviors. Conclusion: The project proposes several solutions and recommends that hospitals implement the AIDET communication process in the daily communication of healthcare staff with patients as a mandatory measure to improve communication and interpersonal skills in all circumstances. Simultaneously, it recommends establishing a steering committee for implementing the AIDET process and developing an implementation plan; organizing training and workshops on communication skills for nurses according to the AIDET process, and organizing regular monitoring and evaluation of implementation.